2021
DOI: 10.1001/jamainternmed.2021.0261
|View full text |Cite
|
Sign up to set email alerts
|

Global Media Coverage of the Benefits and Harms of Early Detection Tests

Abstract: Limitations include use of a measure of EHR work that considers only when clinicians are actively working (thus likely underestimating total time spent on the EHR), a focus on ambulatory practices, an inability to describe the breakdown of after-hours activity, and lack of accounting for time spent by scribes on documentation.The interspecialty differences we have identified are important given the known associations between administrative burden and clinician burnout. Further investigation should seek to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…This sample of Australian journalists seem aware of the potential harms of medical tests such as overdiagnosis, which are often left out of media coverage. 17 But, effectively communicating overdiagnosis is a challenge in light of entrenched beliefs about the benefits of testing and the culture of current journalism practices. Providing journalists with training and support in their efforts to communicate overdiagnosis could aid critical reporting of tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample of Australian journalists seem aware of the potential harms of medical tests such as overdiagnosis, which are often left out of media coverage. 17 But, effectively communicating overdiagnosis is a challenge in light of entrenched beliefs about the benefits of testing and the culture of current journalism practices. Providing journalists with training and support in their efforts to communicate overdiagnosis could aid critical reporting of tests.…”
Section: Discussionmentioning
confidence: 99%
“…The media, through promoting early detection tests to healthy individuals, is considered an important driver. 15 A recent cross-sectional study 17 of global media coverage—including over a thousand media stories about five early detection tests (three-dimensional mammography for breast cancer, liquid biopsy for cancers, Apple Watch for atrial fibrillation, blood biomarker tests and artificial intelligence technology for dementia)—found that the potential benefits of testing were presented far more frequently than potential harms. The risk of overdiagnosis was mentioned in very few stories.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the quality of medical reporting is a crucial endeavour given the powerful influence of the media on the public’s perceptions and usage of healthcare 17 37. This study is part of a global effort to offer journalists more training and support on these challenging issues 36 38.…”
Section: Discussionmentioning
confidence: 99%
“…Overdiagnosis occurs when individuals are labelled with a technically correct diagnosis that does not improve health outcomes or causes more harm than benefit,15 and is now recognised as a key challenge to human health and health system sustainability 16. A recent cross-sectional study of global media coverage of over 1000 media stories about five early detection tests (eg, three-dimensional mammography for breast cancer, liquid biopsy for cancer, blood biomarker tests for dementia) found that the potential benefits of testing were presented far more frequently than any potential harms (97% vs 37%, respectively), and the risk of overdiagnosis was only mentioned in 5% of stories 17. The general public and patients already tend to overestimate the benefits of early detection,14 18 meaning that the media’s often unrealistic and overly optimistic portrayals19 can reinforce these perceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation